Bilateral Optic Neuritis Associated with the Use of Infliximab. (20th November 2011) - Aasly, Jan O.
Abstract : A 40 year old man was admitted with a 2 weeks history of headache, blurred vision and bilateral optic neuritis. During the 6 months period prior to admission he had treated with infliximab infusions for prsoriasis arthritis. He had 0.2 vision in right eye and 0.5 in left Fundoscopy showed moderate disc swelling more on the right than on the left side and right-sided splinter heamorrhages at the disc margin. The intracranial pressure was normal. He was treated with oral methylprednisolone, 100 mg daily for 1 week. His vision improved gradually and when seen 10 weeks later his visual acuity was 1.0 in both eyes and he had normal visual fields. Optic neuritis is a rare but well recognized serious adverse effect of treatments with tumor necrosis factor (TNF) antagonists. This case report illustrates a rare but typical side effect of a TNF alpha inhibitors used for treating a number of inflammatory diseases. These reactions usually appear during first year of treatments and never after the first one or two infusions. Both genders and all ages are affected. In some patients the visual defects are irreversible.